How do you simplify #(a^4c^2e^0)/(b^-1d^-3)# using only positive exponents?

1 Answer
Apr 11, 2016

Answer:

#(a^4c^2e^0)/(b^-1d^-3) = 1a^4bc^2d^3#

Explanation:

#(a^4c^2e^0)/(b^-1d^-3)# to simplify this to all positive exponents there are three aspects of the expression that can be changed

any value to the zero exponent = 1
#e^0=1#

a negative exponent in the denominator can be made positive by moving the value to the numerator #1/b^-1 = b# and #1/d^-3 = d^3#

Therefore
#(a^4c^2e^0)/(b^-1d^-3) = 1a^4bc^2d^3#